Effects of Low Frequency Prefrontal Repetitive Transcranial Magnetic Stimulation on the N2 Amplitude in a GoNogo Task. - Nicola Grossheinrich; Maren Reinl; Oliver Pogarell; Susanne Karch; Christoph Mulert; Monika Brueckl; Kristina Hennig-Fast; Anne Rau; Maria Epple; Ariane Hornig; Frank Padberg (PLoS ONE, 2013)
During the last decade, repetitive transcranial magnetic stimulation (rTMS) of the prefrontal cortex has become established as a treatment for various mental diseases. The rational of prefrontal stimulation has been adapted from the mode of action known from rTMS using motor-evoked potentials though little is known about the precise effect of rTMS at prefrontal sites. The objective of the current study is to investigate the inhibitory effect of prefrontal 1 Hz rTMS by stimulating the generators of event-related potentials (ERP) which are located in the prefrontal cortex. Thus, 1 Hz rTMS was applied offline over the left dorsolateral prefrontal cortex (DLPFC) and the medial prefrontal cortex (MPFC) in 18 healthy subjects who subsequently underwent a GoNogo task. Both active conditions were compared to sham rTMS within a randomized and counterbalanced cross-over design in one day. ERPs were recorded during task performance and the N2 and the P3 were analysed. After 1 Hz rTMS of the left DLPFC (but not of the MPFC), an inhibitory effect on the N2 amplitude was observed, which was related to inhibitory control. In contrast, after 1 Hz rTMS of the MPFC (but not at the left DLPFC) a trend towards an increased P3 amplitude was found. There was no significant modulation of latencies and behavioural data. The results argue in favour of an inhibitory effect of 1 Hz rTMS on N2 amplitudes in a GoNogo task. Our findings suggest that rTMS may mildly modulate prefrontally generated ERP immediately after stimulation, even where behavioural effects are not measurable. Thus, combined rTMS-ERP approaches need to be further established in order to serve as paradigms in experimental neuroscience and clinical research.